(untitled) (Revista de História Regional, 2007)
The present article discusses the viewpoint of Vianinha in the television. In setting out for possible articulations between his teledramaturgy and a national project of culture then debated in the multiple layers of the Brazilian society the research in the end reveals the sense attributed by Vianninha to the working in a media vehicle such as the television. Taking as reference the focuses developed in the creation of the television special series like: O Matador, as to analyses the playwright investiture in a particular language that tries to reveal the impasses lived by the popular class and proposes the politicization of everyday life.